Brain Transport Profiles of Ginsenoside Rb1 by Glucose Transporter 1: In Vitro and in Vivo - Wang, Yu-Zhu; Xu, Qing; Wu, Wei; Liu, Ying; Jiang, Ying; Cai, Qing-Qing; Lv, Qian-Zhou; Li, Xiao-Yu (Frontiers in Pharmacology, 2018)
Ginsenoside Rb1(Rb1) has been demonstrated its protection for central nervous system and is apparently higher distributed to the brain. The objective of this study was to characterize Rb1 transport at the blood-brain barrier(BBB) using primary cultured rat brain microvascular endothelial cells (rBMEC), an in-vitro BBB model. The initial uptake velocity of Rb1 in rBMEC was temperature- and concentration-dependent, and was significantly reduced by phloretin, an inhibitor of GLUT1 transporter, but was independent of metabolic inhibitor. Furthermore, the transport of Rb1 into rBMEC was significantly diminished in the presence of natural substrate α-D-glucose, suggesting a facilitated transport of Rb1via GLUT1 transporter. The impact of GLUT1 on the distribution of Rb1 between brain and plasma was studied experimentally in rats. Administration of phloretin (5mg/kg, i.v.) to normal rats for consecutive one week before Rb1(10mg/kg, i.v.) at 0.5h, 2h, 6h did not alter Rb1 concentrations in plasma, but resulted in significant decreased brain concentrations of Rb1 as compared to in the phloretin-untreated normal rats (489.6±58.3 ng/g versus 105.1±15.1 ng/g,193.8±11.1 ng/g versus 84.8±4.1 ng/g,114.2±24.0 ng/g versus 39.9±4.9 ng/g, respectively). The expression of GLUT1 in the phloretin-treated group by western blotting analysis in vitro and vivo experiments was significantly decreased, indicating that the decreased transport of Rb1 in brain was well related to the down-regulated function and level of GLUT1. Therefore, our in vitro and in vivo results indicate that the transport of Rb1 at the BBB is at least partly mediated by GLUT1 transporter. Keywords: carrier-mediated transporter, drug transport, blood brain barrier , glucose transporter 1, ginsenoside Rb1